Empowering Maritime Graduates for Policy Advocacy and Sustainability in Vocational Education - Damoyanto Purba; Winarno Winarno; Susi Herawati; Hazbi Aziz Ashshiddiqi; Joko Subekti; Andriyan Hendry Ole (Digital Innovation : International Journal of Management, 2024)
This research explores the role of maritime vocational schools in preparing graduates to become effective advocates for policy development and sustainability within the maritime industry. Through qualitative research and descriptive analysis, the study examines the perspectives of maritime professionals, lecturers, graduates, and government officials to assess the effectiveness of current educational programs. The findings highlight strong technical competency development but reveal gaps in policy understanding, leadership skills, and the practical application of sustainability principles. Collaboration between industry and educational institutions is effective, but greater government involvement is needed. To address these challenges, maritime vocational schools must enhance their curricula by incorporating modules on policy advocacy, leadership development, and sustainability. This will ensure that graduates are equipped to influence policy, lead teams, and promote sustainable practices, contributing to the long-term competitiveness and sustainability of the maritime industry.